An exploratory study of perceptions of goal setting support among students at a tertiary institution - C. Chipunza.; N. Masiza (SA Journal of Industrial Psychology, 2004)
The present study explored perceptions of goal setting support among students at a tertiary institution. Seventy-four students in the third year Industrial Psychology and Accounting programme participated in the study. The Goal Setting Support Scale was slightly revised to fit an academic setting and was used to measure perceptions of goal setting support among students in both departments. Results indicated that there were no differences between Industrial Psychology and Accounting students regarding their perceptions of goal setting support. Full time employment prior to enrolment in the university had a significant bearing on the perceptions of goal setting support among students. Opsomming Die teenswoordige studie het die doelstellingsondersteuningspersepsies van studente aan ’n tersiêre instelling ondersoek. Vier-en-sewentig studente in hulle derde jaar in die Bedryfsielkunde en Rekeningkunde programme het aan die studie deelgeneem. Die doelstellingsondersteuningskaal is effens aangepas om die akademiese omgewing te pas en is gebruik om doelstellingsondersteuningspersepsies van studente in beide departemente te meet. Resultate dui aan dat daar geen perseptuele verskille tussen Bedryfsielkunde en Rekeningkunde-studente bestaan ten opsigte van doelstellingsondersteuning nie. Voltydse indiensname voor inskrywing by die instelling het ’n betekenisvolle invloed op die doelstellingsondersteuningspersepsies van studente gehad.